Maternal vaccines: ten considerations for vaccine introduction and scale-up in low- and middle-income countries from the maternal, newborn, child, and adolescent health perspective. Issue 1 (31st December 2022) - Khan, Sadaf; Fleming, Jessica A.; Engmann, Cyril M.
ABSTRACT: Despite significant reduction in childhood mortality, infant – particularly neonatal – mortality continues to be unacceptably high. A substantial proportion of these deaths could be averted by vaccinating mothers during pregnancy (maternal immunization). However, in order to realize the full life-saving potential of maternal immunization, it is important to develop clear introduction and delivery strategies for maternal vaccines. This will necessitate close collaboration between maternal health and immunization stakeholders. This article examines key considerations and areas for action to support successful and sustainable introduction and scale-up of maternal immunization, from the perspective of maternal, newborn, child, and adolescent health stakeholders.